Effect of recombinant bovine somatotropin (bST) on follicular population and on in vitro buffalo embryo production - Filho, M. F. Sa; Carvalho, N. A. T.; Gimenes, L. U.; Torres-Junior, J. R.; Nasser, L. F. T.; Tonhati, Humberto [UNESP]; Garcia, J. M. [UNESP]; Gasparrini, B.; Zicarelli, L.; Baruselli, P. S. (Elsevier B.V., 2009)
The objective of this study was to evaluate the effect of bovine somatotropin (bST) on ovarian follicular population in buffalo heifers and its influence on oocyte quality, recovery rates and in vitro embryo production. We tested the hypothesis that bST treatment in buffalo females submitted to an ovum pick-up (OPU) program Would improve the number of follicles recruited, oocyte quality and in vitro embryo production. A total of 10 heifers were assigned into two treatment groups: group bST (n = 5; receiving 500 mg of bST in regular intervals) and control group (n = 5; without additional treatment). Both groups were subjected to OPU sessions twice a week (every 3 or 4 days), for a total of 10 sessions per female, although due to procedural problems, only the first five OPU sessions produced embryos. The number of follicles and the diameters were recorded at all OPU sessions. The harvested oocytes were counted and classified according to their quality as either A, B, C, D or E, with A and B considered good quality. Cleavage and blastocyst production rates were evaluated 2 and 7 days after in vitro fertilization, respectively. The bST treatment increased the total number of antral follicles (> 3 mm in diameter; 12.2 compared with 8.7: p, < 0.05) and of small antral follicles (< 5 mm; 9.1 compared with 6.5; p < 0.05) per OPU session. The bST also tended to increase the number of oocytes recovered per session (5.2 compared with 4.1; p = 0.07), and enhanced the percentage of good quality oocytes (48.8% compared with 40.6%; p = 0.07), bST showed no effect on cleavage and blastocyst production rates (p > 0.05). The significant effects of performing repeated OPU sessions were decreasing the follicular population (p < 0.001) as well as the number of follicles aspirated (p < 0.001), and oocytes recovered (p < 0.02). In conclusion, bST treatment improves the follicular population, demonstrating its possible application in buffalo donors submitted to OPU programs. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Buffalo-OPU; IGF-I; In vitro embryo production; Bubalus bubalis